Performance of schmitt trigger - Roselyn,, Lim Sheau Chee. (Universiti Malaysia Sarawak, UNIMAS, 2006)
In this project, the designs and the width-length ratio of the transistors affects the performances of the Schmitt Trigger circuit. The proposed design is designed based to the existing Schmitt Trigger which is the Conventional CMOS Schmitt Trigger by manipulating the arrangement of transistors and the width- length ratio. Then, analyses are conducted on the three designs using Microwind at variations of load capacitance and source voltages. Lastly, comparisons are made between the three designs in term of propagation delay, Power-Delay Product and hysteresis voltage